Initial investigation of microplastic pollution in river sediments at Yogyakarta City Indonesia - Inggita Utami; Pidianto Pidianto; Fahmi Hermawan Tricahya; Suci Rahmawati (Sustinere: Journal of Environment and Sustainability, 2021)
Microplastics of less than 5 mm have been widely found in the river sediments that cross the city. Sources of microplastic pollutants can be seen in rivers crossing Yogyakarta City studies on microplastic have never been carried out. This study analyzed the abundance and characteristics of microplastics in river sediments of Yogyakarta City. Data collection was carried out in December 2019 in Winongo River, Code River, and Gadjahwong River. Each sample of the three sediments was taken at each point of the three inlets and outlets in Yogyakarta City. The sediment sample was separated to obtain supernatant-containing microplastics. The abundance of microplastics was quantified and grouped based on the shape, size, and color. Data were analyzed using descriptive and inferential statistics to compare the concentration of microplastic in the three rivers. The results showed that the abundance of microplastics ranged from 279.31 to 1,026.93 particles kg-1, with a higher abundance in the inlet than the outlet. The Code River sediment has the highest microplastic abundance, followed by the Gadjahwong River, and Winongo River. The sediment samples in the rivers crossing Yogyakarta City have been contaminated mainly by the fragment-shaped, transparent, and 1-100 Âµm microplastics.